Forms of cell death and targets at photodynamic therapy - I. V. Reshetov; S. V. Korenev; Yu. S. Romanko (Сибирский онкологический журнал, 2022)
The aim of the study is to study the results of the most significant studies on the forms of tumor cell death and targets in photodynamic therapy (PDT). Material and methods. On the problem, we analyzed the Scopus, WoS, MedLine databases and found 31 sources. Results. PDT is an important tool for studying the pathways leading to the complete devitalization of a malignant tumor. Moreover, subcellular targets in pdt are determined by the properties of photosensitizers (PS). Particularly effective targets are lysosomes and mitochondria, including those for class I PS, photofrin. This explains the effectiveness of photofrin, although it has a weak absorption band in the region of 630 nm with a limited penetration depth into tissues. The development of new PSs with subcellular targets of photofrin, but with an absorption band in the long-wavelength region, is becoming very topical. Such FS are ideal for PDT. Second-generation PSS have already been introduced into clinical practice. The effectiveness of PDT with the use of photoditazine was shown. The mechanisms of action and targets of this PS have been established. The latter include the vessel wall, cytoplasmic membranes, and internal structures of tumor cells. The main type of neoplastic cell death during PDT with photoditazine is direct photocoagulation and ischemic necrosis of the tumor parenchyma due to the destruction of the neoplasm vascular bed. Today, considerable attention is paid to the development of other new PSS, namely, bacteriochlorophyll-α derivatives, which have an intense absorption of radiation in the long-wavelength region of the spectral range. These include the disulfide-bpi conjugate, which contains 2 molecules of dipropoxybacteriopurpurinimide and a cystamine residue, the results of which showed its high efficiency due to the destruction of the tumor vascular bed, the rapid slowdown and/or cessation of cell proliferative activity and their death by necrosis and apoptosis. Rapid progress in studying the mechanisms of action of PDt has shown that autophagy triggering using the lysosomal compartment to degrade and utilize damaged cell organelles and paraptosis associated with defective proteins in the endoplasmic reticulum also play an important role in the elimination of tumor cells. Conclusion. Apoptosis, autophagy, and paraptosis can occur after photodamage to mitochondria, lysosomes, or the endoplasmic reticulum. The balance of cell death pathways is often a determining factor in the effectiveness of PDT.